Analisis Likuiditas Dan Profitabilitas PT. Ace Hardware Indonesia, Tbk - Anugrah, Andi Sri Astuti (Exchall, 2020)
PT. ACE Hardware Indonesia, Tbk is a retail company engaged in home appliances and lifestyle products. The company needs to conduct its financial analysis to ascertain whether the company is able to meet its short-term obligations and detect the company's ability to make a profit. The analytical techniques used in this study are descriptive analysis with liquidity and profitability methods. The results showed that: Liquidity in terms of Current Ratio and Cash Ratio in 2016 was better than in 2015, while in 2017 it decreased compared to 2016. Meanwhile, liquidity in terms of Cash Ratio is getting better than in 2015 and 2016. However, in 2018 liquidity from the Current Ratio aspect decreased. Liquidity in terms of Cash Ratio in 2018 decreased compared to 2017, but the company remains liquid. These findings indicate PT. ACE Hardware Indonesia, Tbk is liquid. Profitability in terms of Gross Profit Margin PT. ACE Hardware Indonesia,Tbk in 2017 was better than 2016 and 2015 but decreased in 2018. Furthermore, profitability in terms of Net Profit Margin in 2016 was better than in 2015 and 2017 and in 2018 there was an increase in Net Profit Margin exceeding NPM in the previous year. These findings indicate PT. ACE Hardware Indonesia, able to make a profit during 2015-2018. Keywords: Liquidity,Current Ratio, Cash Ratio,Profitability, GPM,NPM